SISTEM INFORMASI PENERIMAAN KARYAWAN BARU (PKB): (Studi Kasus : PT.Pou Yuen Indonesia) - Rini Nuraini Sukmana; Ajeng Ima Maulani Rachman (LPPM STMIK BANDUNG, 2021)
Information system is as a system which consists of technology or tools, media used,organized procedures, and human resources which work as a combination to form anorganized system.Recruitment of new employees is one of the processes in the company agency that is usefulfor screening selected prospective employees according to criteria determined by thecompany to become employees. In the process of recruiting new employees at PT. PouYuen Indonesia, it has been done manually or has been computerized but uses MicrosoftOffice Excel. To improve data storage security, automate calculation of test scores, andease of providing new employee recruitment information, an application for newemployee recruitment information systems is needed at PT. Pou Yuen Indonesia.Keywords : Information Systems, Employee Reception, work, police